The wage elasticity of informal care supply: Evidence from the health and retirement study - Olena Y. Nizalova (Institute for the Study of Labor (IZA), 2010)
This paper focuses on the relationship between wages and supply of informal care to elderly parents. Unlike most of the previous research estimating wage elasticities of informal care supply, this study employs instrumental variable technique to account for the fact that the wage rate is likely to be correlated with omitted variables. Based on the data from the 1998 wave of the Health and Retirement Study, the results show that the wage elasticity of informal care supply is negative and larger in magnitude than has been found previously. The lower bound of this elasticity is estimated to be -1.8 for males and -3.6 for females. Additional findings suggest that the wage elasticity of informal care supply differs by the type of care provided to elderly parents, and that it is larger in magnitude among individuals with siblings and those with independently living parents. The analysis also indicates that the reductions in the informal care constitute about 18% of the labor supply response for men and about 56% of the labor supply response for women, which are not compensated by monetary transfers.
Keywords: J22; J18; J14; 330; wage elasticity; informal care supply; labor supply; elderly care; family obligations; Pflegedienst; Familie; Arbeitsangebot; Lohn; Elastizität; Schätzung; USA